Opportunities to strengthen the gender dimension in a Pacific agriculture, nutrition and value chain development project - Herweijer, Rosien; Francis, Judith Ann; Dietershagen, Jana (Technical Centre for Agricultural and Rural Cooperation, 2018)
The aim of this report is to provide a framework for mainstreaming of gender issues throughout all project activities, and to function as an action plan for this purpose within the CTA/IFAD/PIPSO Project ‘Promoting Nutritious Food Systems in the Pacific Islands’. Additionally, in order to ensure proper integration of the gender dimension within the project’s activities, this report chooses a very practical approach with a focus on activity and output level. General guidance presented in this report aims to provide background information and practical ideas to further strengthen the gender dimension of the programme.